2014
DOI: 10.1016/j.prosdent.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of in vitro biofilms formed on denture base resin

Abstract: Photodynamic therapy was effective in reducing E coli counts on biofilms formed on acrylic resin specimens. The inhibition of microorganism growth tended to be directly proportional to the amount of energy provided by the light-emitting diode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…Thus, the present scheme of illumination would also be suitable for in vivo application. In previous studies on LED-based in vitro aPDT against P. aeruginosa, light intensities in the range of 100 -200 mW cm À2 were used (2,11,26). The intensity used in our study (45 mW cm À2 ) is lower than those values, and the lower intensity was possible due to the effects of the additives.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the present scheme of illumination would also be suitable for in vivo application. In previous studies on LED-based in vitro aPDT against P. aeruginosa, light intensities in the range of 100 -200 mW cm À2 were used (2,11,26). The intensity used in our study (45 mW cm À2 ) is lower than those values, and the lower intensity was possible due to the effects of the additives.…”
Section: Discussionmentioning
confidence: 94%
“…Methylene blue (MB), a cationic photosensitizer, has been widely used for aPDT because of its low cost and efficacy against a broad spectrum of both Gram-positive (+) and Gramnegative (À) bacteria. MB has been reported to be safe for use in humans (10,11). Cell death caused by aPDT depends on the probability of a dye adhering to the outside of the cell membrane and permeating across the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple bacterial biofilms have been shown to be eradicated using diode lasers (405–940 nm) and different photosensitizers on acrylic resin, glass, titanium, and zirconia, which in some cases was shown to be synergistic with antibiotic treatment [163, 167, 168, 169, 170, 171, 172, 173, 174]. LEDs (385–660 nm) have also been used to inhibit and eradicate bacterial formation on silicone coupons, dental implant surface, acrylic resin and titanium [162, 168, 175, 176, 177, 178, 179, 180]. A wide range of light in the electromagnetic spectrum has been shown to be useful in destroying bacteria, including the higher energy UVC and blue light, when combined with antibiotics [170].…”
Section: Main Textmentioning
confidence: 99%
“…Several methods of disinfection have been suggested 3 , 5 , 28 , mainly including immersion of dentures in chemical solutions of sodium hypochlorite, alkaline glutaraldehyde, 4% chlorhexidine, chlorine dioxide, and denture cleansers such as alkaline peroxides, herbal and photodynamic therapy 1 , 11 , 13 , 15 . However, past studies have indicated that such solutions affect the physico-mechanical properties of the materials used to construct removable prostheses 19 , 25 .…”
Section: Introductionmentioning
confidence: 99%